"…I've said I wish I was dead, you'd be better off without me": A systematic review of people's experiences of living with severe asthma. (4th March 2019) - Eassey, Daniela; Reddel, Helen K.; Foster, Juliet M.; Kirkpatrick, Susan; Locock, Louise; Ryan, Kath; Smith, Lorraine
ABSTRACT: Objective : Our aim was to conduct a systematic review and synthesis of qualitative evidence exploring the lived experience of adults with severe asthma. Data sources : We searched MEDLINE via OvidSP, PsycINFO via OvidSP, PubMed, CINAHL, EMBASE, Sociological Abstracts, Google Scholar, the journals Qualitative Health Research and Qualitative Research, and a study of experiences of living with asthma by the Health Experiences Research group. Study selections : Studies were included if they used qualitative methods and explored the subjective experiences of adults (≥18 years) with a clear diagnosis of severe asthma. Results : From 575 identified studies, five met the inclusion criteria. Synthesis revealed an overarching theme of efforts that people living with severe asthma engage in to achieve personal control over their condition. Individuals 'strive for autonomy' through dealing with symptoms and treatment, acquiring knowledge, making decisions and reclaiming identity. Conclusion : This systematic review found a paucity of qualitative studies reporting on people's perspectives of living with severe asthma, and a focus on clinical rather than personal issues. Our synthesis reveals that severe asthma was disempowering, and a threat to identity and life roles. What was important to people living with severe asthma was striving to achieve a greater level of personal control over their condition, but these efforts received little support from their healthcare providers. Thus, more attention should be paid to understanding the self-management strategies and personal goals of people living with severe asthma. This may assist in designing interventions to better support patient self-management and improve health outcomes.